Identifying and prioritising services in European terrestrial and freshwater ecosystems - Paula A. Harrison; Marie Vandewalle; Martin T. Sykes; Pam M. Berry; Rob Bugter; Francesco de Bello; Christian K. Feld; Ulf Grandin; Richard Harrington; John R. Haslett; Rob H. G. Jongman; Gary W. Luck; et al. (Biodiversity and Conservation, 2010)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.